Science, religion and nationalism
1 online resource.
Keywords: ""Science" and "Religion" have been two major elements in the building of modern nation-states. While contemporary historiography of science has studied the interactions between nation building and the construction of modern scientific and technological institutions, "science-and-religion" is still largely based on a supposed universal historiography in which global notions of "science" and of "religion" are seldom challenged. This book explores the interface between science, religion and nationalism at a local level, paying attention to the roles religious institutions, specific confessional traditions or an undefined notion of "religion" played in the construction of modern science in national contexts: the use of anti-clerical rhetoric as scapegoat for a perceived scientific and technological backwardness; the part of religious tropes in the emergence of a sense of belonging in new states; the creation of "invented traditions" that included religious and scientific myths so as to promote new identities; the struggles among different confessional traditions in their claims to pre-eminence within a specific nation-state, etc. Moreover, the chapters in this book illuminate the processes by which religious myths and institutions were largely substituted by stories of progress in science and technology which often contributed to nationalistic ideologies"--